Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada Pt Perusahaan Perkebunan Lonsum Di Kabupaten Bulukumba Periode 2020-2024 - Eza Ramadhani; Nurhidayah Nurhidayah; Ismawati Ismawati (Akbis: Media Riset Akuntansi dan Bisnis, 2026)
The purpose of this research is to assess PT Perusahaan Perkebunan London Sumatra Indonesia Tbk's (LONSUM) financial performance from 2020 to 2024. Descriptive quantitative research methodology is employed, utilizing secondary data from the company's official website in the form of yearly financial statements. Based on the availability of complete financial report items during the course of the five-year observation period, purposive sampling was used as the sample strategy. Four primary financial ratios were computed as part of the data analysis process: liquidity, solvency, profitability, and activity. The results show that PT LONSUM maintains excellent financial performance in terms of liquidity and solvency. The Current Ratio is well above industry standards, indicating a strong ability to meet short-term obligations. Low solvency ratios (DER and DR) reflect a healthy capital structure and minimal debt dependency. Regarding profitability, the company demonstrates fairly good and stable performance despite global commodity price fluctuations, with an increasing trend at the end of the period. However, in terms of activity ratios, the Total Asset Turnover (TATO) was found to be suboptimal, even though inventory management (ITO) remains efficient. Overall, PT LONSUM exhibits financial resilience and high adaptability to the dynamics of the plantation industry, although optimization of biological and fixed asset utilization is required to increase future sales volume.